Practices of capital structure decisions: Malaysia survey evidence - Mat Nor, Fauzias; Ibrahim, Khairunisah; Haron, Razali; Ibrahim , Izani; Alias, Mohd Adnan (World Business Institute, 2012)
How firms make their corporate financing decisions has been one of the most extensively researched areas in corporate finance. Yet there is little consensus on how firms choose their capital structure. This study examines the capital structure practices of the Malaysian CFOs by employing a survey analysis on the non-financial listed firms in Malaysia, conducted from November 2010 to March 2011. 203 usable responses from the Malaysian CFOs were obtained, thus representing a response rate of 25%. This study is to analytically identify how the capital structure choices are influenced by those who make the decisions in practice. The survey result provides mixed support for the notion that firms does trade-off costs and benefits to derive an optimal debt ratio. From the financing hierarchy point of view, this study finds that Malaysian managers regard the use of internal funds for financing projects as the most important source of financing. This study enriches the literature by discovering the extent to which the capital structure theories are able to explain the corporate financing behavior and practices of Malaysian managers.